Стратегічні напрями розвитку транскордонного співробітництва “Україна-Польща” - Дриль, О. І. (Видавництво Львівської політехніки, 2014)
Проаналізовано напрями налагодження спільної транскордонної співпраці між Україною та Польщею, проведено SWOT-аналіз транскордонного регіону та визначено на його основі стратегічні пріоритети розвитку транскордонного співробітництва України та Польщі. Актуалізується значення туризму для розвитку транскордонного співробітництва українсько-польських прикордонних регіонів та визначено напрями його розвитку. The trends of establishing joint cross-border cooperation between Ukraine and Poland are analysed in the article. Since in the process of cross-border cooperation some spheres dominate over the others, there is a need to distinguish the strategic ones to ensure the competitiveness of cross-border region. Both countries have a number of common features, thus favourable conditions for establishing close cooperation between border regions in different areas are formed. SWOT-analysis of cross-border region has been performed to reason and identify perspectives of cooperation. On the basis of this analysis the strategic priorities for the development of cross-border cooperation between Ukraine and Poland have been determined. The importance of tourism for the development of cross-border cooperation of Ukrainian-Polish border regions has been emphasized as well as axes of its development has been determined.
Strategic axes of Ukrainian-Polish cross-border сooperation
Keywords: cпівробітництво; прикордонні регіони; туризм; екологія; кластери; cooperation; border regions; tourism; ecology; clusters